Cyclotides: Overview and biotechnological applications - Gould, Andrew (Chembiochem, 2017)
Cyclotides are globular microproteins with a unique head-to-tail cyclized backbone, stabilized by three disulfide bonds forming a cystine knot. This unique circular backbone topology and knotted arrangement of three disulfide bonds makes them exceptionally stable to chemical, thermal and biological degradation compared to other peptides of similar size. In addition, cyclotides have been shown to be highly tolerant to sequence variability aside from the conserved residues forming the cystine knot. Cyclotides can also cross cellular membranes and are able to modulate intracellular protein-protein interactions both in vitro and in vivo. All these features make cyclotides appear as highly promising leads or frameworks for the design of peptide-based diagnostic and therapeutic tools. This article provides an overview on cyclotides and their applications as molecular imaging agents and peptide-based therapeutics.